The Role of Immunotherapy to Overcome Resistance in Viral-Associated Head and Neck Cancer - Pharaon, Rebecca R.; Xing, Yan; Agulnik, Mark; Villaflor, Victoria M. (Frontiers in Oncology, 2021)
A subset of head and neck cancers arising in the oropharynx and the nasopharynx are associated with human papillomavirus or Epstein-Barr virus. Unfortunately, limited treatment options exist once patients develop recurrent or metastatic disease in these cancers. Interest has risen in utilizing novel strategies including combination immune checkpoint inhibitors, vaccines, and adoptive cellular therapy, to improve treatment response and outcomes. Several ongoing studies are investigating the potential to overcome resistance to standard of care chemoradiation therapy with monotherapy or combination immunotherapy strategies in these viral-associated head and neck cancers.